2013
DOI: 10.1074/jbc.m112.441535
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Envelope Composition Determines the Ability of Neutrophil-type Cells to Passage through Micron-scale Constrictions

Abstract: Background: The unusual nuclear shape of neutrophils has been speculated to facilitate their passage through confined spaces. Results: Levels of nuclear protein lamin A modulate cell passage through micron-scale pores. Conclusion:The unique protein composition of neutrophil nuclei facilitates their deformation; lobulated nuclear shape is not essential. Significance: Altered nuclear envelope composition, as reported in cancer cells, could impact cell passage through physiological gaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
330
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 288 publications
(364 citation statements)
references
References 49 publications
26
330
4
1
Order By: Relevance
“…Considering plasticity associated with chromatin structure (40), we captured the effects of irreversible nuclear shape changes (Fig. 5) and verified recent observations suggesting that cells lacking lamin A/C are more deformable and undergo more plastic deformations (34).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Considering plasticity associated with chromatin structure (40), we captured the effects of irreversible nuclear shape changes (Fig. 5) and verified recent observations suggesting that cells lacking lamin A/C are more deformable and undergo more plastic deformations (34).…”
Section: Discussionsupporting
confidence: 77%
“…Experimentally, it has been shown that the nuclei of cells lacking lamin A/C exhibit larger irreversible shape changes after moving through tight spaces (25,34) (Fig. 5 c, right).…”
Section: Effects Of Plasticity On Irreversible Nuclear Deformationsmentioning
confidence: 93%
See 1 more Smart Citation
“…We speculated that these changes in protein level caused nuclear lobulation and deformability of the granulocytic nuclei. [19][20][21][22][23][24]31,32 As can be seen in Fig. 2 and Supplemental Table 2, there is a dramatic difference in transcript level of LMNA between the 2 differentiated cell forms, with significant decrease following RA, versus a significant increase following TPA.…”
Section: Nuclear Envelope and Cytoskeletal Proteinsmentioning
confidence: 95%
“…18 In addition, karyotype differences are documented later in the present study. Our laboratory has published extensively on HL-60/S4 in an investigation of nuclear shape, chromatin structure and cytoskeletal changes during differentiation induced by RA, TPA and vitamin D3 (e.g., [19][20][21][22][23][24][25] ). In our hands, HL-60/ S4 cells have proven to be robust and to yield highly reproducible cell differentiation.…”
Section: Introductionmentioning
confidence: 99%